RANCANG BANGUN SISTEM INVENTORY BERAS MENGGUNAKAN PHP DAN MYSQL PADA CV AGUNG JAYA SUKOHARJO - Rina Ayu Tri Asmara (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2021)
CV AGUNG JAYA Sukoharjo is a place of business engaged in the sale of rice. Currently, rice stock data management is still done manually. Recording of each entry and exit of rice using a ledger or still with a bookkeeping system. This study aims to design and build a rice inventory system that can manage buying and selling rice, rice stocks, and recapitulation in a structured and manageable way in one application. The method used in this study uses a waterfall approach. The waterfall method is used to develop a system by having a sequential flow starting from analysis, design, compiling code, and testing. The system design uses (UML) Unified Medelling Lenguage. This research produces a rice inventory system application that has a menu of sales, purchases, reports, warehouses, lists of suppliers and consumers. The results of the webequal test are obtained from 4 factors such as Usability Quality, Information Quality, Service Interaction, and Overall, the value of the total website quality is 74.2%